2013
DOI: 10.2337/dc12-2661
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Skin Intrinsic Fluorescence With Type 1 Diabetes Complications in the DCCT/EDIC Study

Abstract: OBJECTIVETo determine whether skin intrinsic fluorescence (SIF) is associated with long-term complications of type 1 diabetes (T1D) and, if so, whether it is independent of chronic glycemic exposure and previous intensive therapy.RESEARCH DESIGN AND METHODSWe studied 1,185 (92%) of 1,289 active Diabetes Control and Complications Trial (DCCT)/Epidemiology of Diabetes Interventions and Complications (EDIC) participants from 2010 to 2011. SIF was determined using a fluorescence spectrometer and related cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 39 publications
4
70
2
Order By: Relevance
“…The non-significant association with these outcomes is due to the low power to detect small effects, since we have good power for detecting an OR >1.50 for a sustained AER >30 mg/24 h with α = 0.05 [15]. In line with this, the rs1495741 G-allele has previously been associated (OR 1.06, p  = 2 × 10 −5 ) with an increased risk of coronary artery disease (CAD) [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-significant association with these outcomes is due to the low power to detect small effects, since we have good power for detecting an OR >1.50 for a sustained AER >30 mg/24 h with α = 0.05 [15]. In line with this, the rs1495741 G-allele has previously been associated (OR 1.06, p  = 2 × 10 −5 ) with an increased risk of coronary artery disease (CAD) [36].…”
Section: Discussionmentioning
confidence: 99%
“…SIF excited with a light-emitting diode (LED) centred at 375 nm, and emission detected over 435–655 nm (with the reflectance adjusted by the dimensionless exCitation and emission exponents, k x  = 0.6, k m  = 0.2, respectively), referred to as SIF1, was the primary outcome [15, 18]. In secondary analyses, we examined SIFs measured using excitation LEDs centred at 405 nm, 416 nm, 435 nm and 456 nm (SIF2–SIF15; ESM Table 6).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of seven studies showed that skin autofluorescence was positively associated with mortality, neuropathy, nephropathy, and cardiovascular events (79). Certain studies found that skin autofluorescence predicted microvascular and macrovascular complications of diabetes independent of HbA 1c (80,81), whereas others found that adjustment for HbA 1c rendered these associations nonsignificant (82). These discrepant findings are possibly accounted for by differences in the patient population and statistical methods.…”
Section: Agesmentioning
confidence: 99%
“…Noninvasively assessed skin AGEs were also associated with retinopathy in the DCCT/EDIC cohort [173]. Skin collagen AGEs measured biochemically on skin biopsies were independent predictors of diabetic retinopathy (and other microvascular complications) in the DCCT/EDIC cohort [174][175].…”
Section: Factors Related To Advanced Glycation Endproducts (Ages)mentioning
confidence: 85%
“…Many studies in diverse ethnic groups have demonstrated correlations between skin AGEs measured non-invasively or biochemically and concurrent retinopathy status, including its presence and/or severity [66,70,169,[171][172][173]. Noninvasively assessed skin AGEs were also associated with retinopathy in the DCCT/EDIC cohort [173].…”
Section: Factors Related To Advanced Glycation Endproducts (Ages)mentioning
confidence: 99%